(1 + cot A + tan A) (sin A - cos A) = sin A tan A - cot A cos A
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
tan A = , cot A =
Consider the left side
(1 + cotA + tanA)(sinA - cosA)
each term in the second factor is multiplied by each term in the first factor.
1(sinA - cosA) + cotA(sinA - cosA) + tanA(sinA - cosA)
= sinA - cosA + cosA - + - sinA ( collect like terms )
= -
= ( sinA × ) - ( × cosA )
= sinAtanA - cotAcosA
= right side ⇒ proven
True
False
Answer:
true
Step-by-step explanation:
Answer:
true
Step-by-step explanation:
To represent the situation, you would have to do 14÷3 because there are 3 cats that eat 14 pounds of food in a week and to figure out how much a cat eats in a week, you would have to divide.
Answer:
305.5
Step-by-step explanation:
350.75 + 250.25 = 601
601 - 295.50 = 305.50